PVDF/PMMA membranes for lemon juice clarification: fouling analysis - Firman, Leticia Raquel (2015)
Microfiltration/ultrafiltration membranes with different degrees of hydrophilicity and structural characteristics from poly(vinylidene fluoride) (PVDF), polymethylmetacrylate (PMMA), and polyvinylpirrolidone (PVP) in dimethylformamide (DMF) solvent were prepared to be used in the lemon juice clarification. The effect of transmembrane pressure (Δp = 0.4–1 bar) and tangential feed velocity (v = 0.2–1 m/s) on permeate flux and juice quality at T = 20°C was examined. The membrane containing 15% of PVDF, 5% PMMA, and 5% PVP (mean pore radii rpm= 0.25 μm and porosity ε = 0.25) achieved the best performance at Δp = 1 bar and v = 1 m/s, with a final permeate flux at quasi-steady state of 32.5 (L/hm2). The clarified lemon juice presented physical, chemical, and nutritional characteristics comparable to the fresh lemon juice, and 100% of total solid rejection. Membrane fouling was evaluated by applying different fouling models. Results indicated that a good fitting correlation between the experimental data and both complete blocking and cake models was achieved.